Effect of heat-killed Lacticaseibacillus paracasei KW3110 on mild to moderate seasonal allergic rhinitis symptoms in Japanese adults: a randomized, double-blind, placebo-controlled parallel-group study - Sugihara, Yoshihiko; Zheng, Jiawen; Fukushima, Yuko; Nozawa, Hajime; Ushida, Yusuke; Tsuji, Ryohei; Okamoto, Yoshitaka; Fujiwara, Daisuke (Frontiers in Nutrition, 2025)
BackgroundIn recent years, the prevalence of seasonal allergic rhinitis has increased rapidly in Japan, becoming a social problem. Therefore, we evaluated the effect of tablets containing Lacticaseibacillus paracasei KW3110 (L. paracasei KW3110) on allergic symptoms in the nose and eyes.MethodsIn a randomized, double-blind, placebo-controlled, parallel-group study, 120 healthy adults with mild to moderate allergic rhinitis ingested either a placebo tablet or a test tablet containing L. paracasei KW3110 for 12 weeks (from January to April). Subjects who did not regularly use medication and experienced nasal and eye discomfort in early spring were selected. Allergic symptoms in the nose and eyes were assessed using subjective symptom surveys and diagnosis by an otorhinolaryngologist.ResultsCompared with the placebo group, the L. paracasei KW3110 group showed a significant improvement in the score of “nasal symptoms” (p < 0.05) and “outdoor activities” (p < 0.05) in the Japanese Rhino-conjunctivitis Quality of Life Questionnaire (JRQLQ No.1) at 4 weeks when pollen dispersal begins, and “runny nose” (p < 0.05) in a diary questionnaire on nasal and eye symptoms at 8 weeks. Diagnosis by an otorhinolaryngologist showed a significant decrease in the score of “paroxysmal sneezing or rhinorrhea” (p < 0.05) and “classification of severity of allergic rhinitis symptoms” (p < 0.05) at 4 weeks, and the number of subjects scoring “worse” (p < 0.05) in the efficacy assessment.ConclusionThese findings suggest that intake of L. paracasei KW3110 is effective in alleviating nasal symptoms in subjects with mild to moderate allergic rhinitis, which can be useful for preventing allergic rhinitis without medication.Clinical trial registrationhttps://www.umin.ac.jp/, identifier UMIN000053239.